PENGARUH EXPERIENTIAL MARKETING TERHADAP KEPUASAN PELANGGAN - Wardana, Reza Yudha; Puspaningrum, Astrid (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Customer satisfaction plays an important role in business. It is based on the fulfilment of customers’ wants and needs from products or services they have received because customers will be satisfied by products and services that suits their needs and preferences. Experiential marketing enables customers to distinguish certain products or services from the others because they can feel or get direct experiences. This type of marketing is used by companies or marketers in packaging their products, by which they can offer emotional experiences that touch customer’s heart and feelings. The objective of this research is to identify the effect of experiential marketing on the satisfaction of Coffee Shop’s customers. A number of 100 respondents was selected through the use of purposive sampling, to whom 5-point Likert-scaled questionnaires were distributed to acquire the primary data. The results of the multiple linear regression analysis performed in SPSS 22 have led to the finding that experiential marketing significantly influences customer satisfaction.